2005
DOI: 10.2174/1574088054583381
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of High Throughput Screening at G Protein Coupled Receptors

Abstract: Technologies used for high throughput screening (HTS) at G protein coupled receptors (GPCRs) comprise two major approaches; those generally conducted measuring signal intensity changes using a microtiter plate format, and those measuring cellular protein redistribution via imaging-based analysis systems. Several homogeneous assays, i.e. those without wash and fluid phase separation steps, measure changes of second messenger signaling molecules including cAMP, Ins P 3 and calcium. Imaging based assays determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Available literature suggested that potent and even modestly selective activators of D1 that lack the catecholamine motif are rare, although recent reports by Bristol-Myers Squibb and Astellas Pharma have disclosed the discovery of non-catecholamine D1-selective positive allosteric modulators (PAMs). In our effort to identify novel activators of this recalcitrant target, we opted to run a high-throughput screen (HTS) . The HTS was run using cAMP homogeneous time-resolved fluorescence (HTRF) kits from Cisbio.…”
Section: Resultsmentioning
confidence: 99%
“…Available literature suggested that potent and even modestly selective activators of D1 that lack the catecholamine motif are rare, although recent reports by Bristol-Myers Squibb and Astellas Pharma have disclosed the discovery of non-catecholamine D1-selective positive allosteric modulators (PAMs). In our effort to identify novel activators of this recalcitrant target, we opted to run a high-throughput screen (HTS) . The HTS was run using cAMP homogeneous time-resolved fluorescence (HTRF) kits from Cisbio.…”
Section: Resultsmentioning
confidence: 99%